Review on dry reforming of methane, a potentially more environmentally-friendly approach to the increasing natural gas exploitation - Lavoie, Jean-Michel (Frontiers in Chemistry, 2014)
With the actual growth of the natural gas industry in the US as well as the potential and availability of this non-renewable carbon source worldwide, reforming of methane gas is getting increasing attention. Methane can be used for the production of heat or electricity, as well, it can be converted to syngas, a building block that could lead to the production of liquid fuels and chemical, a very promising pathway in light of the increasing price of oil. Amongst the different reforming techniques, dry reforming could represent a very interesting approach both to valorize a cheap source or carbon (CO2) as well as to reduce the overall carbon footprint of the increasing worldwide fossil-based methane consumption. In this short review, attention will be given on the thermodynamics of dry reforming followed by an investigation on dry reforming using heterogeneous catalyst by focusing on the mots popular elements used in literature for dry reforming. Attention will as well be given to different other emerging techniques that may allow countering at one point the high thermodynamic penalties that accompanies conversion of methane using carbon dioxide.